الطاقة الكهربائية في العراق الواقع وآفاق المستقبل (المجلة العراقية للعلوم الاقتصادية, 2018)
The electricity sector is the main pillar of the national economy, and that the development of various economic sectors must rely on it as input in all economic activities. The individual consumption rate of electricity is an important criterion in assessing the level of welfare of the individual and society. The power crisis in Iraq has been accumulated after decades of destruction caused by the policies of the previous political system, and the apparent corruption after 2003. This has led to large spending amounted to more than 40 billion dollars annually due to lack of electricity, In addition to environmental pollution and damage to public health.The problem of electricity described as dysfunctional relationship between decreasing electrical energy and the demand for electricity, which is growing at an increasing rate. The research aims to analyze the reality of the electricity sector and its potential, as well as the development of our future vision for it until 2017.